2013
DOI: 10.1128/jb.02285-12
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Pan-Genomes of Escherichia coli, Shigella spp., and Salmonella enterica

Abstract: cMultiple sequencing of genomes belonging to a bacterial species allows one to analyze and compare statistics and dynamics of the gene complements of species, their pan-genomes. Here, we analyzed multiple genomes of Escherichia coli, Shigella spp., and Salmonella enterica. We demonstrate that the distribution of the number of genomes harboring a gene is well approximated by a sum of two power functions, describing frequent genes (present in many strains) and rare genes (present in few strains). The virtual abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
108
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 38 publications
8
108
2
1
Order By: Relevance
“…To identify genes differentially distributed between the E. coli and Shigella genomes, a large-scale BSR (LS-BSR) analysis was performed on 69 E. coli and 69 Shigella genomes (45). The results demonstrate that several genes, primarily associated with metabolism, are conserved in E. coli isolates and largely absent (n Ͻ 2) in Shigella isolates (Table 2); this stands in contrast to a recent study which suggested that no genes could be used to distinguish the two groups (47). In fact, some of the genes identified as being differentially present in E. coli and not in Shigella have been previously identified as being pathoadaptive for Shigella (48), suggesting that the analysis is valid.…”
Section: Pan-genome Comparisons Betweencontrasting
confidence: 51%
“…To identify genes differentially distributed between the E. coli and Shigella genomes, a large-scale BSR (LS-BSR) analysis was performed on 69 E. coli and 69 Shigella genomes (45). The results demonstrate that several genes, primarily associated with metabolism, are conserved in E. coli isolates and largely absent (n Ͻ 2) in Shigella isolates (Table 2); this stands in contrast to a recent study which suggested that no genes could be used to distinguish the two groups (47). In fact, some of the genes identified as being differentially present in E. coli and not in Shigella have been previously identified as being pathoadaptive for Shigella (48), suggesting that the analysis is valid.…”
Section: Pan-genome Comparisons Betweencontrasting
confidence: 51%
“…To be able to determine population structure without relying on limited or biased sets of pan‐genomes (Gordienko et al , 2013), we explored the natural genomic variation of the human gut microbiome (Schloissnig et al , 2013; Luo et al , 2015; Nayfach et al , 2016; Lloyd‐Price et al , 2017; Truong et al , 2017). To this end, we assessed the microbial genetic landscape of 2,144 deeply sequenced human stool metagenomes from nine countries, spanning three continents, including published (Huttenhower et al , 2012; Qin et al , 2012; Karlsson et al , 2013; Le Chatelier et al , 2013; Zeller et al , 2014) as well as 298 newly generated ones (Table EV1).…”
Section: Resultsmentioning
confidence: 99%
“…(Johnson et al , 2006), for which specific subspecies are specialized for different environmental conditions (Biller et al , 2014). In regard to the human microbiome, extensive work has been undertaken to characterize population structure and describe subspecies in species that include pathogenic bacteria, such as Escherichia coli , different Salmonella species, and a few others, for which multiple typing schemes exist (Gordienko et al , 2013; Chakraborty et al , 2015; Bale et al , 2016; Sharma et al , 2016), but not for the vast majority of human gut commensals.…”
Section: Introductionmentioning
confidence: 99%
“…The unique genome is heavily enriched in genes related to mobile elements (62%), with the other categories being poorly represented. This high proportion of mobile elements in the unique genome is similar to other organisms, including E. coli, and indicates that horizontal gene transfer (HGT) has had a large effect on S. aureus evolution (25)(26)(27). Indeed, the archaic MRSA clone, thought to be the ancestor strain of MRSA in Europe, obtained its methicillin resistance because of the horizontal transfer of the mecA gene from an unknown source (1).…”
Section: Size and Content Of The Core Genome Provide Insight Into Essmentioning
confidence: 90%